MEMAHAMI PROSEDUR PENELITIAN KUALITATIF: Panduan Praktis untuk Memudahkan Mahasiswa - Nursanjaya Nursanjaya (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
Qualitative research is a systematic and analytic research or research that builds a cultural reconstruction of a group of people where the culture is a reflection of the view of the human group as a whole society. Qualitative research is still relatively foreign to most lecturers and students. In fact, this research is as scientific as quantitative research, although with a different meaning. Qualitative research arises because there is a change in the paradigm in viewing a reality, phenomenon or symptom. In this paradigm, social reality is seen as something holistic, complex, dynamic, and full of meaning.